Experience and Challenges during Establishment of a Cyclotron and PET-CT facility at National Institute of Nuclear Medicine & Allied Sciences (NINMAS) (Bangladesh Journal of Nuclear Medicine, 2021)
Abstract not availableBangladesh J. Nuclear Med. 22(2): 137-140, Jul 2019